2013
DOI: 10.1016/j.biopsych.2012.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The Addictive Dimensionality of Obesity

Abstract: Our brains are hardwired to respond and seek immediate rewards. Thus, it is not surprising that many people overeat, which in some can result in obesity, whereas others take drugs, which in some can result in addiction. Though food intake and body weight are under homeostatic regulation, when highly palatable food is available, the ability to resist the urge to eat hinges on self-control. There is no homeostatic regulator to check the intake of drugs (including alcohol); thus, regulation of drug consumption is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
236
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(283 citation statements)
references
References 110 publications
13
236
0
10
Order By: Relevance
“…Some have proposed that pre-existing hypoactivity of mesocorticolimbic systems produces 'reward deficiency' that drives over-eating (Johnson and Kenny, 2010;Parylak et al, 2011). By contrast, others propose that opposite hyperreactivity of these systems drives elevated cue-triggered motivation to eat (Davis et al, 2009;Gearhardt et al, 2011;Stice et al, 2012;Volkow et al, 2013a). Both hypotheses recognize that individual differences are important (Berthoud, 2012); indeed differences in sensitivity to leptin, insulin, and post-meal satiety have been associated with susceptibility to diet-induced obesity (Levin et al, 2004;Clegg et al, 2005;Cottone et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some have proposed that pre-existing hypoactivity of mesocorticolimbic systems produces 'reward deficiency' that drives over-eating (Johnson and Kenny, 2010;Parylak et al, 2011). By contrast, others propose that opposite hyperreactivity of these systems drives elevated cue-triggered motivation to eat (Davis et al, 2009;Gearhardt et al, 2011;Stice et al, 2012;Volkow et al, 2013a). Both hypotheses recognize that individual differences are important (Berthoud, 2012); indeed differences in sensitivity to leptin, insulin, and post-meal satiety have been associated with susceptibility to diet-induced obesity (Levin et al, 2004;Clegg et al, 2005;Cottone et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Differential consumption among groups is unfortunately a common byproduct of many alcohol self-administration models, and considering the caloric content of the gelatin mixture, could result in differential effects on reward circuitry. The consumption of high fat or other 'rich' diets can alter reward circuitry (eg, Volkow et al, 2013); however, this requires extended access to these foods (Johnson and Kenny, 2010), resulting in differential weight gain between groups. We did not observe any differences in body weight between groups (during adolescence or in adulthood), which therefore suggests that even the 'high' levels of gelatin consumption by our control animals were not high enough to result in physiological differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…While no studies of baseline extracellular DA levels and total DA D2 receptor levels, which would require PET studies of DA D2 receptors before and following DA depletion, have been reported in obese humans, animal studies have shown decreased baseline extracellular DA levels, decreased amphetamine induced DA release, and decreased absolute levels of DA D2 receptor levels in obese animals, particularly in those who compulsively consume food (16)(17)(18). Both Stankowska and other investigators have postulated that extreme obesity may be due to a food addiction and that extremely obese humans may have changes in DA neurotransmission similar to those seen in substance abuse (26,27,50). Studies in human substance abusers have shown both decreased extracellular DA levels, and total DA D2 receptor levels as well as decreased psychostimulant induced DA release and available DA D2 receptor levels (21)(22)(23)(24)(25).…”
Section: Obesity Dopamine and Reward Behaviorsmentioning
confidence: 99%